MEMBERSAMAI ALUMNI MENINGKATKAN POTENSI DIRI PREGNANCY MASSAGE ENTERPRENEURSHIP - Ririn Indriani; Susanti Pratamaningtyas; Dwi Estuning Rahayu (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
Community Service is empowered to produce young entrepreneurs who are innovative and creative in the field of Midwifery Science, not only able to create jobs for themselves but also able to open new jobs for others, especially alumni who are still not lucky enough to get jobs that match their profession. or self-employed or in groups. The creation of jobs by means of entrepreneurship can ease the burden on the state in opening new jobs. Community service activities carried out at this time are still in the first year stage. So it is planned for the second and third years to be continued with different participants. Result: Pregnancy massage training skills for alumni are the right choice to provide opportunities for alumni to open new business opportunities. The results of community service activities which also serve as evaluation activities for community service activities are obtained from the value of the pre test (done before giving the material), post test (done after giving the material) which has increased the value of good knowledge from 0 to 10 people (58.83%) has increased , collection of assignments to make videos about Pregnancy Massage, and make a business plan for Pregnancy Massage Entrepreneurship. Conclusion: Pregnancy massage skills open up new job opportunities